UPAYA GURU DALAM MENGEMBANGKAN PEMAHAMAN KONSEP KEPADA ANAK DIDIK DALAM PEMBAHASAN TRIGONOMETRI - Joko Sulianto (Universitas PGRI Semarang, 2011)
Concepts are ideas that can be used to categorize or classify objects, whether a particular objects is an example of the concepts or not. At the simplest level we often observe objects with their characteristic. Based on the observation that the similarities can be seen from the object, so we can classify these objects.Concept math learning can be done by using a deductive approach begins by giving definitions, axioms, and the theorems followed by giving examples. This example can be given by the teacher or found by students. Deductive approach in teaching mathematics is commonly practiced. Learning by using deductive approach have to do fastly so it caan be more efficient. If a math lesson conducted with formal approach, but its implementation is deviate from the formal system, so it use informal approach. In this approach, theorem or formulas of mathematics is given. Then used to solve the problem without degrading or prove prior learning with informal approach can be used to train the students to discover and prove the characteristic or formula.